The Experiences of EFL Teachers Teaching English Skills and Contents in the Midst of Covid-19 Pandemic - Kenny Lestari; Langgeng Budianto (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2022)
The major purpose of this research was to obtain the voices of EFL senior teachers regarding the use of the WhatsApp- group tool. The researchers applied a qualitative method design by practicing two instruments: semi-structured interview and indirect observation. The case study design was undertaken by engaging two EFL senior teachers who actively implemented the WhatsApp group tool in the learning process in the midst of the outbreak of COVID-19. Four designs of qualitative frameworks were convenience aspect (ease of use) and usefulness aspect (Interaction and motivation), educational aspect, and technical aspect was simultaneously utilized to draw their experience in teaching English skills and content courses. The result of research discussions declared that the EFL teachers claimed the different voices toward the utilizing WhatsApp-group tool. Grammar lecturers claimed that this digital tool is a learning management system, integrating the tools for educational aims, and perceiving advantages in boosting the effectiveness and efficiency of the teaching and learning process. In addition, Grammar lecturers as educators emphasized to their learners that the young generation does not only learn the academic aspects but also build a good attitude, critically-thinking, social caring, and high tolerance the society. The learning strategy is well-known as the maternity reflective method. In contrast, the Prose lecturer claimed several obstacles; junk notifications, flooding irrelevant chats in the WhatsApp forum, poor signal, and consuming extra time. Furthermore, he added that interactions in the WhatsApp-group tool as supportive learning cannot boost learners to be active due to some factors. This evidence became a significant challenge in applying WhatsApp as a management teaching media. Thus, the pedagogical implication of utilizing WhatsApp- group L tool in EFL classroom should be carefully tackled to minimize the overuse of this mobile application